Inovasi Media dan Alat Permainan Edukatif Islami untuk Pengembangan Motorik Anak Usia Dini - Zukhairina Zukhairina; Lilis Putri Yani; Ani Purwati; Nurul Khoni’ah; Nur Yanti; Leni Marlina (Jurnal Ilmu Pendidikan, 2026)
Early childhood motor development is a fundamental aspect that influences future physical, cognitive, and social abilities. This study examines innovations in educational media and games (EGA) based on Islamic values ​​to optimize early childhood motor development. Using a literature review method, this study analyzed journal articles, books, and research reports published between 2018 and 2024. The results indicate that the integration of Islamic values ​​in EGA not only improves children's gross and fine motor skills but also strengthens religious identity and Islamic character from an early age. The innovations developed include hijaiyah letter puzzles, mosque blocks, prayer games, and interactive digital media based on applications. The findings indicate that Islamic EGA designed with developmentally appropriate practice (DAP) principles can improve eye-hand coordination by 78%, body balance by 82%, and fine motor skills by 75%. This study recommends the development of more varied Islamic EGA, the integration of learning technology, and training of early childhood teachers in the use of Islamic-based educational media.